1998
DOI: 10.1590/s0036-46651998000100012
|View full text |Cite
|
Sign up to set email alerts
|

Use of doxycycline for leptospirosis after high-risk exposure in São Paulo, Brazil

Abstract: A clinical trial pilot study, double-blinded, randomized, and controlled with a placebo to assess the effectiveness of oral doxycycline (200 mg, single dose) in preventing leptospirosis after high exposure to potentially contaminated water was performed in São Paulo, SP, Brazil. Confirmed cases were defined as those with leptospira IgM antibody and symptoms; asymptomatic cases were those presenting with IgM antibodies but no symptoms; and suspected cases were individuals with symptoms but no IgM antibody. Fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 5 publications
1
49
0
2
Order By: Relevance
“…However, the apparently low risk should not preclude the use of penicillin (620). Doxycycline (200 mg orally, once weekly) has been shown to be effective for short-term prophylaxis in high-risk environments (245,511,551). Similar findings have been reported in rhesus monkeys challenged experimentally (199).…”
Section: Treatmentmentioning
confidence: 66%
“…However, the apparently low risk should not preclude the use of penicillin (620). Doxycycline (200 mg orally, once weekly) has been shown to be effective for short-term prophylaxis in high-risk environments (245,511,551). Similar findings have been reported in rhesus monkeys challenged experimentally (199).…”
Section: Treatmentmentioning
confidence: 66%
“…3,4,7,8,22,23 In addition, several studies suggest that doxycycline could be used either as chemoprophylaxis or as post-exposure prophylaxis and post-exposure empirical treatment. 21,[24][25][26][27] Both a study of U.S. Army soldiers who participated in a 3-week training exercise in the jungles of Panama and another study in residents of a rural area of the Andaman Islands found preventive efficacy of doxycycline, administered 200 mg once weekly. 24,25 Administration of doxycycline, 100 mg daily, represent an alternative chemoprophylaxis, in areas where malaria and leptospirosis are endemic, as suggested by the preventive efficacy of such treatment during the race in Borneo.…”
Section: Discussionmentioning
confidence: 99%
“…The use of post-exposure chemoprophylaxis has been studied in Brazil for rural residents with high-risk exposure to pathogenic leptospires and should be evaluated for asymptomatic athletes after the identification of cases of leptospirosis. 26,28 In following, this study would not recommend empiric self-treatment of febrile travelers and rather advise them to seek medical attention as a first course, considering the broad spectrum of tropical diseases causing acute febrile illness, such as malaria and arbovirus. 29 Sporting events and ecotourism in tropical areas are increasing and travelers are exposed to a wide range of pathogens, some of them exclusively tropical but also pathogens of worldwide distribution such as leptospirosis, whose incidence is even higher following periods of heavy rainfall and flooding.…”
Section: Discussionmentioning
confidence: 99%
“…Erythromycin has also been found effective in severe leptospirosis [57]. Injection of Hydrocortisone 100 mg every 8 hourly is also given in severe cases [60]. Antibiotic therapy should be completed for 7 d except for azithromycin dihydrate which could be given for 3 d [6].…”
Section: Treatment and Prophylaxismentioning
confidence: 99%
“…Antibiotic therapy should be completed for 7 d except for azithromycin dihydrate which could be given for 3 d [6]. Doxycycline (hydrochloride and hyclate) has been used as a chemoprophylactic agent for short time exposure, but it cannot be recommended for continuous routine use or for a long-term occupational exposure [60]. The duration of prophylaxis depends on the degree of exposure and the presence of wounds.…”
Section: Treatment and Prophylaxismentioning
confidence: 99%